Влияние вакуумно-дуговой ионно-лучевой обработки на структуру и механические свойства стали 30ХГСН2А - Панин С. В. Сергей Викторович; Власов И. В. Илья Викторович; Сергеев В. П. Виктор Петрович; Овечкин Б. Б. Борис Борисович; Любутин П. С. Павел Степанович; Рамасуббу С. Сундер; Миронов Ю. П. Юрий Петрович; Марущак П. О. Павел Орестович (2015, 2015)
Заглавие с экрана